Efeitos da sucessão ecológica na estruturação de taxocenoses de lagartos em áreas de caatinga - Rocha, Stéphanie Menezes (2018)
This study is divided into three chapters. In the first, we present a list of lizards for the Alto Sertão region of Sergipe, Brazil. In total, we registered 19 species from 10 families, with Ameivula ocellifera, Tropidurus hispidus and Tropidurus semitaeniatus the most abundant species. In the second chapter, we investigate the structure patterns in a lizard assemblage from Canindé de São Francisco, Sergipe. We inventoried 13 species belonging to seven families. The lizards proved to be experts in the use of microhabitat and diet, with the exception of T. hispidus and A. ocellifera. Still, we verified that the assemblage is structured as to the use of the space and trophic resources, being its patterns influenced by ecological factors, more prominent, and historical. Finally, we found a joint and balanced effect between ecology and phylogeny on the morphometric axis. In the third and last chapter we investigate the effects of ecological succession on the structuring of lizard assemblage in a semiarid area of Caatinga habitat from the Alto Sertão region, Sergipe. In total, we registered 8034 lizards, belonging to 16 species and nine families. The lizards total abundances did not vary between the analyzed successional stages (initial, intermediate and late). Species richness and composition were statistically different only between the early and late stages. Regarding the spatial niche, only the early stage assemblages was not structured, but all of them were more influenced by recent ecological factors. As for the food niche, we found structure in all assemblages, with the formation of an increasing gradient of organization with the progression of succession and the influence of both ecological and historical factors, the latter, however, weaker than the first. Finally, we detected phylogenetic structuring only in the initial stage and in relation to the MNTD index. As its standardized form (NTI) proved to be negative, the verified structure came from ecological interactions and not from the action of phylogeny in its formation.